On-Sight and Red-Point Climbing: Changes in Performance and Route-Finding Ability in Male Advanced Climbers - Limonta, Eloisa; Fanchini, Maurizio; Rampichini, Susanna; Cé, Emiliano; Longo, Stefano; Coratella, Giuseppe; Esposito, Fabio (Frontiers in Psychology, 2020)
Aim. In lead climbing, the ascent of the route can be defined as on-sight or red-point. On-sight is the purest and hardest style of ascent since it provides a greater physiological and psychological commitment. However, still little has been studied about the differences between the two mode of ascent, especially on advanced climbers. To optimize the performance, both in on-sight than in red-point climbing, route preview capacity and movements sequence recall are the essential skills. Therefore, this study aims: i) to compare the performance during on-sight and red-point ascent in advanced climbers; ii) to evaluate how change the route preview capacity and movement sequences recall, before and after an on-sight and red-point performance. Methods. Eighteen male advanced climbers (age 29.2±4.7 years, body mass 67.8±3.6 kg, stature 175.2±2.4 cm, best red-point and on-sight grades 7b+/8a and 7a+/7b+) were video-recorded during the route ascent in the two styles to evaluate the performance and to count the static and dynamic actions times. Each of them underwent a test, before and after the two ascents, to assess its route interpretation (RI) capacity and movement sequence recall and complete a questionnaire to evaluate the level of anxiety. During and after the performance, the heart rate (fH), lactate concentration, ([La-]), rate of perceived exertion (RPE) were detected. Results. i) An improvement in performance was observed in red-point style, compared to on-sight. The ascent was faster (148.7±13.6 s and 179.5±12.5 s, respectively, P<0.05), smoother (significant reduction in exploratory moves and in stops times, P<0.05), less demanding physiologically (lower fHpeak and [La-]peak, P<0.05) and psychologically (lower RPE, cognitive and somatic anxiety and higher self-confidence, P<0.05). ii) The RI capacity improves in red-point respect to on-sight style and, in the same style, between pre and post ascent. Conclusions. Red-point style is confirmed to be less demanding than the on-sight one, both physiological and psychological, in advanced climbers too. Our results denote the trainable character of the route interpretation ability and highlight the importance to include in the training programs the specific techniques to improve the interaction between perceptual, psychological and physiological factors.